Literasi Digital dan Pendidikan Pemilih Generasi Z dengan Media Permainan Kartu - Rahman, Taufiqur; Muktaf, Zein Mufarrih; Tunggali, Ade Putranto Prasetyo Wijiharto; Pradipta, Elita Putri (Jurnal Pengabdian Masyarakat - PIMAS, 2024)
Social media is currently widely used to discuss politics and the resulting discourse often polarizes society. In addition to the issue of political polarization, an important issue that needs to be observed ahead of, during and after the election is the circulation of hoaxes, fake news, and hate speech between supporters of political candidates. According to the results of the Kompas R&D survey, the interest of Generation Z is large enough to use the right to vote in the 2024 election. However, their enthusiasm tends to be lower when compared to the generation above them. If in Generation Z the enthusiasm rate is at 67.8 percent, then the participants of the generation above have a percentage of 68.1-77.9 percent. For this reason, it is necessary to have alternative media that can be used as a vehicle for political education for generation Z so that their enthusiasm to participate in elections is increasing. This community service team has developed a card game as an alternative media for voter education among generation z. The result of the event using this game shows an increase of understanding of the participants from 43,33 point to 67,65 point in average out of 17 participants of the event.